The Dynamics of Academic Buoyancy in Contemporary Education - Eslami, Fereydon; Hooshmandi , Roodabeh (KMAN Counseling & Psychology Nexus, 2023)
The study aims to explore the dynamics of academic buoyancy within contemporary education, focusing on how it influences educational outcomes, the mechanisms behind its development, and effective strategies for fostering resilience among students. This narrative review synthesized findings from empirical studies, theoretical papers, and case analyses published between January 2000 and December 2023, using an exhaustive search across multiple academic databases. The selection criteria focused on studies discussing academic buoyancy in K-12 and higher education settings, with thematic analysis used to identify key themes. Research identified predictors of academic buoyancy, such as academic self-efficacy and lower levels of test anxiety, and examined its mechanisms, including its role in students’ emotional and cognitive responses to academic challenges. The outcomes of academic buoyancy were found to include enhanced academic performance, engagement, and psychological well-being. Academic buoyancy plays a critical role in students’ educational experiences, influencing their ability to navigate academic challenges. Future research should delve deeper into its mechanisms and outcomes, with educational practice incorporating strategies to foster resilience and adaptability among students across diverse settings.